Entrepreneurial orientation, total quality management and performance in the hotel sector of Baja California: a quantitative study - Ibarra Cisneros, Manuel Alejandro; Vela Reyna , Juan Benito; Ríos Nequis , Eric Israel (Acta Universitaria, 2022)
The article aims to analyze the relationship between entrepreneurial orientation and performance of the hotel sector in the state of Baja California, Mexico, and the mediating effect of total quality management. The study adopts a quantitative, explanatory, cross-sectional approach, using the structural equation model through partial least squares as a statistical technique, applied to 94 hotels with three and more stars in the state during 2020. The results indicate that entrepreneurial orientation influences hotel performance, and that total quality management has a mediating effect on this relationship. It is concluded that a philosophy based on customer satisfaction, innovation, and continuous improvement of quality allows hotels to improve their status and competitiveness. The main limitation of the study was its cross-sectional nature.